Plurality of Elements Constituting the Law - Fernández Sessarego, Carlos (1973)
Throughout this work, the author offers an integral and multidimensional vision of Law, focusing on the presence of three elements that integrate it: human conduct, norms and values. In this context, the importance of considering the ontological, estimative, and logical layers is emphasized in order to adequately grasp the complexity of the "legal", emphasizing that Law cannot be reduced to any of its elements in isolation, but emerges from their integration in an inseparable synthesis. Thus, this three-dimensional theory based on the triplicity of elements results in conceiving Law as the integration of human conduct in its dimension of coexistence, realization of legal values, and representation through norms that establish imputative judgments of duty to be. Finally, the author reflects on the vocation of placing Law at the service of man, criticizing unidimensional perspectives and advocating a personalist vision of Law as a dynamic factor of social transformation.